Modification of chemical and hydrophysical properties of two texturally differentiated soils due to varying magnitudes of added biochar - Ajayi, A.E; Horn, R. (Soil & tillage research, 2016)
•Woodchip biochar improved chemical and hydraulic properties of 2 soils.•Improvement is commensurate to amount of added biochar.•Interparticle bonding and resilience of aggregate was enhanced up to ≤50gkg−1.•Amendment rate beyond 50gkg−1 did not make additional useful impact. The potential benefit of biochar as a soil conditioner to improve crop yield and simultaneously sequester carbon in the soil, is a subject of intense discourse. Biochar amendment of agricultural soils is presumed to improve water holding capacity of the soil, and enhance nutrient retention within the root zone. However, there are very few investigations which provide quantitative data and qualitative descriptions concerning the specific mechanisms driving these improvements in the properties of biochar-amended soils. In this study, the effect of different rates of biochar amendment on some chemical, physical and hydraulic properties of fine-sand and sandy loamy silt soils was investigated by adding 20, 50 and 100g biochar kg−1 (by dry weight). In order to evaluate the additional effects of biochar application, the initial hydrophobicity and rheological properties were also examined. The result showed that biochar amendment improved total carbon and aggregate properties. The available water capacity was significantly higher in the amended substrates, particularly in the amended fine sand. Saturated hydraulic conductivity of the sandy loam silt increased between 25% and 119%, but decreased in the fine-sand between 23 and 82%. Moreover, biochar amendment of the sandy loamy silt improved particle to particle bonding and resulted in the development of weaker (compared with the unamended control) but more resilient aggregates which were better structured. With increasing rate of added biochar (≥50–≤100gkg−1) the added biochar itself now dominated the internal soil strength of the substrate. Adding (≥20gkg−1) biochar, to the fine-sand induced particle rearrangements, which in combination with possible surface oxidation at the biochar-soil particles interphase, improved bonding in this originally non-cohesive soil. Beyond an amendment rate of 50g biochar kg−1 soil, we observed that most of the positive improvements, associated with the biochar treatment of the soils, were no longer significant and the aggregates became brittle and collapsed more easily. Our results therefore provide more detailed insights into the effect of biochar in agricultural soils depending on texture of the soil and the amount of added biochar.